Gender Equality in Natural Disasters and Climate Change - Odjoe, Mintje Ratoe; Fanggidae, Rolland Epafras; Amtiran, Paulina Y. (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2020)
Climate change will contribute to increasing the frequency and severity of natural disasters with negative impacts on human life. Although disasters and climate change affect all populations, the impact on each gender, in terms of vulnerability, ability, and resilience, will be different. The impact of disasters and climate change is certainly heavier on women and children because women will struggle more to overcome the effects and have limited access to resource management. This research questions how women are affected by climate change and natural disasters and how climate change impacts trade work. The findings suggested that a new approach is needed for climate change, disaster management, and gender equality. This study examines traditional culinary traders at Oesapa Color Beach, most of whom are women victims of high waves destroying their place for business.